THE ROLE OF INFORMATION SYSTEMS IN THE DEVELOPMENT OF SOCIAL ENTREPRENEURSHIP - Andrejeva, Sabīne; Ežmale, Sandra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
Social entrepreneurship promotes not only business development but also solves social problems. In order to promote the development of social enterprises, organization needs to use information systems. By using information systems effectively, organization can, for example, reach a wider range of consumers, establish cooperation with other companies or explore market competition. The aim of the research is to evaluate the role of information systems in the development of social entrepreneurship.